Mr. Squashash: A feasibility study on squash fritters - Daryl Joy R. Barican, Leemwell U. Canaria, Lhoel Jay P. Cardino, Aliya Monica G. Dela Paz, Francess C. Regio 4 0 16; 5
u
Undergraduate Thesis: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2